The diagnosis that should speak its name: why it is ethically right to diagnose and treat personality disorder during adolescence - Hutsebaut, Joost; Clarke, Sharon L.; Chanen, Andrew M. (Frontiers in Psychiatry, 2023)
Although national guidelines explicitly state that personality disorder can be diagnosed and treated in young people aged 12 to 18 years (adolescents), most clinicians remain hesitant. This creates a gap between science and practice, which we argue is largely motivated by moral reasons and, therefore, is best challenged by ethical arguments. We provide seven arguments in support of the notion that it is ethically right to diagnose and treat personality disorder when it occurs in adolescents. Central to these arguments is the scientific evidence that features of personality disorder are among the best predictors of a complex cluster of psychopathology leading to impairments in many areas of current and future mental, social and vocational functioning. We argue that intervention during adolescence and young adulthood is not only humane, but also critical for efforts to avert the longstanding psychosocial and health problems that seem refractory to treatment in adults with personality disorder. Moreover, we argue that regular services are often inadequately equipped to meet the needs of young people with personality disorder and that the common ‘stepped-care’ approach should be replaced by a ‘staged-care’ approach. Finally, we argue that early detection and intervention might have anti-stigmatizing effects, similar to other areas of healthcare in which stigmatizing labels have changed meaning when the conditions to which they refer have become more amenable to treatment.